Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Complete mitochondrial genomes and phylogenetic analysis of three species of Indo-Pacific freshwater gobies, Stiphodon (Gobiiformes, Oxudercidae) - Cheng-He Sun; Xian-Ru Li; Su-Fan Zhou; Yan-Zi Zhong; Xiao Ma; Xiao-Die Chen (Journal of Genetics, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Chronic intermittent hypoxia sustains the low-grade inflammatory memory of monocytes via activation of myelopoiesis - Shi Qi Li; Yi Wang; Meng Yao Li; Liu Zhang; Xi Xi Chen; Ying Ni Lin; Li Na Zhou; Xian Wen Sun; Yong Jie Ding; Qing Yun Li (Inflammation Research, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Ventilation-driven bioaerosol dispersion and surface deposition in respiratory wards: Implications for healthcare worker protection and targeted disinfection - Fan Liu; Shuhua Yu; Yanjing Ren; Qin Jia; Xian Li; Chongyang Zhang; Chanjuan Sun (Building and Environment, 2026)

Increased soil-plant system N retention in a warming climate through chemical niche partitioning between plants and microorganisms in an alpine meadow on the Tibetan Plateau - Fei Peng; Xiaojie Chen; Jianbo Sun; Mengting Hu; Chimin Lai; Ben Chen; Xingzhi Xu; Xian Xue; Chengyang Li; Yuxin Xie; Carly Stevens; Yanfu Bai; et al. (Biology and Fertility of Soils, 2026)

In situ SIMS Pb-Pb dating of aeschynite reveals Early Paleozoic Nb mineralization at Bayan Obo - Bo Yang; Li Yang; Zhao Yan; Qing Sun; Yu Liu; Xiao-Xiao Ling; Xin-Yu Hou; Yong-Gang Zhao; Guo-Ying Yan; Jian-Yong Liu; Xian-Hua Li (Science Bulletin, 2026)

Differential distribution characteristics of heavy metal resistance genes and driving mechanisms of heavy metal speciation in river-lake system sediments - Yihan Chen; Yunan Sun; Yongjie Yang; Shuanggang Hu; Kangping Cui; Chao Zhu; Xian-Zhong Fu; Chen-Xuan Li; Peng Jiang; Qianli Huang (Journal of Hazardous Materials, 2026)

NR1H4 downregulation facilitates abnormal cell proliferation contributing to IgA nephropathy pathogenesis, with potential clinical implications - Xian Li; Wen Yang; Changxi Sun (Human Cell, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Conceptual design of a surface-underwater unmanned vehicle and fluid characteristics analysis during surface navigation - Zhen Xu; Yuanhao Li; Shiye Xian; Haitong Zhao; Tianli Liu; Shaoqiong Yang; Tongshuai Sun (Ocean Engineering, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effect of perovskite A-site disorder on its activity in solid-state CO2 electrolysis - Shuo Liu; Lin-Bo Liu; Biao Ouyang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Jing-Li Luo; Subiao Liu (Chemical Engineering Journal, 2026)

Plant uptake of available N from different layers varies among species in an alpine meadow of permafrost regions on the Qinghai-Tibetan Plateau - Fei Peng; Jianbo Sun; Chimin Lai; Weisong Liu; Chengyang Li; Xiaojie Chen; Ben Chen; Xian Xue; Ji Chen; Carly Stevens (Soil Ecology Letters, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Zinc leaching from low-grade oxide ores in NH3-(NH4)2CO3 medium: Thermodynamics, kinetics, and process analysis - Qiyou Chen; Jinlei Yang; Baohua Sun; Shiyan Wu; Bingjie Jin; Yuhui Zhang; Wenkai Liang; Xian Zhong; Longyu He; Ruixue Yang; Dong Li; Yao Deng (Chemical Engineering Journal, 2026)

To expand or not to expand? An LCA of the environmental sustainability of China's tunnel-greenhouse shrimp farming - Yue Sun; Jinying Yu; Xiaohan Yang; Lei Jia; Dengpan Dong; Meng Li; Xiefa Song; Xian Li (Aquacultural Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Electronic modulation of nitride/hydroxide heterostructure for long-lasting urea oxidation reaction over 1000 h - Xian-Jun Niu; Guang-Sheng Qian; Yang Bai; Shen-Bing Sun; Lei Zhou; Wei-Yong Jiao; Ji-Sen Li (Chemical Engineering Journal, 2026)

Retinal spectral sensitivity and neurotransmitter-mediated light preferences in turbot (Scophthalmus maximus): A novel strategy for optimizing spatial efficiency in intensive aquaculture - Wen Sun; Lele Wu; Feng Liu; Xin Li; Jiale Zhou; Xian Li (Aquaculture, 2026)

Alstoniaschines A‒I, nine undescribed alkaloids from Alstonia scholaris and their potential medicinal effects on diabetic nephropathy - Wen-Jie Sun; Shi-Shi Qin; Xian-Run Wu; Yun-Li Zhao; Xu-Jie Qin; Xiao-Dong Luo (Phytochemistry, 2026)

Cadmium accumulation and isotope fractionation in soil–oilseed rape (Brassica napus L.) system in a typical Karst region - Weihai Yu; Guangyi Sun; Heng Yao; Xian Wu; Zhe Liu; Yu Lin; Yu Cheng; Jiang Li; Hua Zhang; Xinbin Feng (Journal of Hazardous Materials, 2026)

Thermal decomposition of lignin under hydrogen atmosphere: A ReaxFF molecular dynamics study - Linjia Yin; Tan Li; Hong Xian; Jing Su; Bingyan Sun; Zhongyang Luo; Heping Li; Muye Feng; Guanqun Luo; Kaige Wang (Fuel, 2026)

Study on deformation and failure characteristics of jointed surrounding rock using a physical model composed by interlooking blocks - Bing-jun Sun; Wei-teng Li; Yu-chun Mei; Xian-feng Yin; Yang Li; Ting-chun Li (Bulletin of Engineering Geology and the Environment, 2026)

A Transformer-based framework with generative spectral augmentation for online monitoring of hyaluronic acid fermentation - Weilu Tian; Lixuan Zang; Yunyi Li; Cheng Peng; Jinhua Zhang; Huarong Shao; Ruiqing Xian; Ru Sun; Fei Liu; Haining Tan; Peixue Ling (Carbohydrate Polymers, 2025)

Characterization of the complete mitogenomes of Synodontis decorus and Synodontis petricola (Teleostei: Mochokidae) with a phylogenetic analysis of the Mochokidae family - Cheng-He Sun; Xian-Ru Li; Yi-Jing Zhan; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

Complete mitochondrial genome sequence of Nannostomus eques and comparative analysis with Nannostomus beckfordi - Xian-Ru Li; Cheng-He Sun; Yi-Jing Zhan; Shuang-Xi Jia; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

The association between urinary levels of organic phosphorus insecticide exposure and subclinical thyroid disorders - Gaohui Wei; Yi Shen; Xian Wang; Dandan Xiong; Lingli Zhang; Tianliang Zhao; Xinjie Li; Mengmeng Sun; Sihui Yu; Xueqi Huang; Shengkang Cao; Ning Liao; et al. (Toxicology Letters, 2025)

Cu nanowire arrays on electroless deposited cu foam for efficient electrocatalytic formaldehyde selective conversion to co-produce H2 and valuable chemicals - Chunyi Ye; Yang Yang; Shujing Chen; Chunhua Liu; Xiao-Qing Sun; Danni Liu; Jiujun Zhang; Jing-Li Luo; Xian-Zhu Fu (Chemical Engineering Journal, 2025)

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Synergistic enhancement of Pt electrocatalyst stability and activity in hydrogen oxidation reaction by polyoxometalate and carbon dot co-boosting - Fei-Yang Yu; Zhong-Ling Lang; Xian Wang; Jing Sun; Yu-Chen Liu; Hua-Qiao Tan; Jun-Jie Ge; Yang-Guang Li; Zhen-Hui Kang (Science Bulletin, 2025)

Experimental and mechanistic study on the removal of elemental mercury in coal-fired flue gas by SO2-modified activated coke within a wide temperature range - Lingxuan Chen; Guangqian Luo; Mingyu Yu; Chunhui Sun; Yi Xiao; Yongda Huang; Sheng Chen; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Fuel, 2025)

One-pot synthesis of injectable freeze-dried platelet lysate functionalized peptides hydrogel for pressure ulcers repair - Kun Liu; Lei Wang; Dongdong Li; Fengying Qi; Shaoduo Yan; Xiaoyang Yi; Yanhong Li; Yuyuan Ma; Xian Su; Yuxin Zhang; Xunuo Li; Ruotong Zhang; et al. (Chemical Engineering Journal, 2025)

C-Phycocyanin mitigates alcoholic liver injury in mice via gut microbiota informatics and liver metabolomics - Lin Sun; Meng Zhao; Xian Yang; Xinyue Li; Xiaomei Wang; Zhongshan Zhang (Algal Research, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Anecic earthworm enhanced the soil multifunctionality by affecting soil bacterial abundant taxa - Yan Hu; Bing-Jie Jin; Xin-Yuan Li; Qing-Lin Chen; Cheng-Liang Sun; Gang Li; Xian-Yong Lin (Soil Ecology Letters, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Identification of key feature variables and prediction of harmful algal blooms in a water diversion lake based on interpretable machine learning - Yundong Wu; Bo Xian; Xiaowei Xiang; Fang Fang; Fuhao Chu; Xingkang Deng; Qing Hu; Xiuqiong Sun; Wei Tang; Shaopan Bao; Genbao Li; Tao Fang (Environmental Research, 2025)

Microbial inoculant-induced modifications of rhizospheric metabolites and microbial communities enhance plant growth - Hui Nie; Yuxuan Shi; Xinxin Yang; Jingyi Zeng; Yingzhou Tang; Xin Liu; Lianhao Sun; Yuexiang Zhou; Xian Xu; Manda Liu; Chong Li; Jinchi Zhang (Plant and Soil, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Selective separation of cyclopentane and cyclohexane derivatives with molecular size differences by polystyrene divinylbenzene resin DCE-3A - Zhiyi Xu; Zhuofeng Sheng; Shaojuan Chen; Shuhua Li; Yaojie Liu; Long Jiang; Weizhi Sun; Chao Xu; Mo Xian (Journal of Environmental Chemical Engineering, 2025)

Ultra-low temperature removal of element mercury in coal-fired flue gas by activated carbon - Renjie Zou; Tong Sun; Guangqian Luo; Lingxuan Chen; Li Wang; Sheng Chen; Shiqing Wang; Xian Li; Ping Xiao; Hong Yao (Fuel, 2025)

Managing Aquaculture Noise: Impacts on Fish Hearing, Welfare, and Mitigation Strategies - Shanshan Duan; Raquel O. Vasconcelos; Lele Wu; Xin Li; Wen Sun; Xian Li (Reviews in Aquaculture, 2025)
As intensive aquaculture continues to develop, substantial investments have been made in equipment to sustain high‐density farming. However, this has resulted in elevated noise levels within these aquaculture environments, particularly below 2000 Hz, matching the hearing range of most cultured fish species. Fish under noise conditions may experience hearing loss and physiological stress, which can negatively affect their growth, foraging efficiency, reproductive success, and increase their susceptibility to diseases. These adverse effects compromise the welfare of cultured fish, potentially decreasing production quality and increasing mortality rates. Despite these notable effects, the understanding and management of noise conditions in aquaculture systems lag behind other environmental parameters in terms of recognition and control. In this review, we cover the fundamentals of fish auditory systems, the hearing range of key cultured fish species, and the most common noise sources and levels prevalent in current intensive aquaculture systems. Additionally, we examine recent discoveries on the effects of anthropogenic noise on fish hearing, physiological responses, and behavior. Finally, we provide strategies for noise monitoring and management in the aquaculture industry, while also highlighting open questions for future research. Our goal is to assist researchers and practitioners in comprehending underwater noise and its effects on cultured fish species, providing a valuable resource for promoting the healthy and sustainable development of intensive aquaculture.

Isolation and identification of a novel bisacodyl analogue, bisacodyl dicycloproyl carboxylate, as a potential illegal additive in a dried plum product advertised for weight loss - Xian-Xian Li; Feng Jiang; Hong Yu; Xiao-Jing Huang; Jing-Xian Zhang; Jin-Tao Xia; Ying-ying Ran; Fan Huang; Jian Sun; Qing Hu (Food Additives & Contaminants: Part A, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Cobalt-catalyzed reversible deposition/dissolution of MnO2 for enhancing the long-cycle stability of aqueous Zn-Mn batteries - Changpeng Xian; Ruilin He; Qianwei Chen; Qiulin Li; Yandong Ma; Shu-juan Bao; Wei Sun; Hao Chen; Maowen Xu (Chemical Engineering Journal, 2025)

Numerical study on a new floating breakwater with openings, arc-shaped wings, and plates using the SPH method - Shi-Xian Wu; Peng-Nan Sun; Qing-Yang Li; Matteo Rubinato; Jian-Qiao Chen (Ocean Engineering, 2025)

Enhancing nitrogen conversion and reducing N2O emission in actual dyeing wastewater with low C/N ratio by addition of kitchen waste leachate - Jiachao Yao; Jiamo Sun; Wu Zhou; Xian Cheng; Weidong Li; Jun Chen (Journal of Environmental Chemical Engineering, 2025)

From 3D pedestrian networks to wheelable networks: An automatic wheelability assessment method for high-density urban areas using contrastive deep learning of smartphone point clouds - Siyuan Meng; Xian Su; Guibo Sun; Maosu Li; Fan Xue (Computers, Environment and Urban Systems, 2025)

How can ecosystem services trade-offs/synergies help select the optimal cultivated land restoration pattern? A study based on multi-scenario simulations - Xian Zhao; Wei Sun; Shiqin Zhang; Yinan Yang; Yixuan Yang; Hailian Lan; Tao Yu; Xiangyun Li; Yujing Xie (Applied Geography, 2025)

A novel and flexible way to derive water quality criteria for copper - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Science of The Total Environment, 2025)

Twin deformable point convolutions for airborne laser scanning point cloud classification - Yong-Qiang Mao; Hanbo Bi; Xuexue Li; Kaiqiang Chen; Zhirui Wang; Xian Sun; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

FEC-driven surface conversion reaction to construct lithiophilic and air-stabilized LLZTO for durable lithium battery - Qiulin Li; Zhi Xiao; Kang Pu; Yandong Ma; Changpeng Xian; Wei Sun; Maowen Xu; Shu-Juan Bao (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Dual Hydrogen-Producing Formaldehyde-Water fuel cell for pollutant treatment and valuable chemical Co-generation - Yang Yang; Jianwen Liu; Munir Ahmad; Xiao-Qing Sun; Chunhua Liu; Shujing Chen; Jiujun Zhang; Jing-Li Luo; Xian-Zhu Fu (Chemical Engineering Journal, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Integrating sentinel-2a imagery, DEM data, and spectral feature analysis for landslide detection via fully convolutional networks - Yu Qu; Hanfa Xing; Lin Sun; Xian Shi; Jianfeng Huang; Zurui Ao; Zexiu Chang; Jiaju Li (Landslides, 2025)

Correction: Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2025)

Simulation and experimental study on splitting performance of Rectifier Nozzle Type Critical Distributor for multi-parallel evaporators - Xiaofeng Li; Wenfu Zhang; Zhili Sun; Di Liang; Lei Yan; Haiwang Zhao; Jiale Chen; Fumin Hou; Xian Lv; Dandan Wang; Jiangman Yan (International Journal of Refrigeration, 2025)

Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2024)

Research on effective mercury removal from flue gas over Cl/Br/I/O modified adsorbents at ultra-low temperature - Lingxuan Chen; Ruize Sun; Guangqian Luo; Tong Sun; Li Wang; Leicong Liang; Yulu Zhang; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Carboxymethyl chitosan/peach gum polysaccharide packaging film incorporating Citrus sinensis essential oil effectively enhances the quality preservation of strawberries - Maolin Liu; Chunjie He; Wendan Chen; Yushu Li; Ningwei Yang; Xuqing Chen; Jing Xue; Xian Wang; Anxiang Lu; Zongda Xu; Xiuhai Zhang; Lei Sun; et al. (Food Packaging and Shelf Life, 2024)

Derivation of marine water quality criteria for copper based on artificial neural network model - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Environmental Pollution, 2024)

Influence of low-temperature pyrolysis pretreatment on the co-combustion performance of coal and waste polyvinyl chloride/tire - Mengli Zhou; Yang Xu; Guangqian Luo; Ruize Sun; Renjie Zou; Chunhui Sun; Xian Li; Hong Yao (Fuel, 2024)

Research on mercury re-release model in wet flue gas desulfurization (WFGD) in coal-fired power plants - Ruize Sun; Mingyu Yu; Guangqian Luo; Li Wang; Mengli Zhou; Xinpei Lu; Xian Li; Hong Yao (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Effects of Combined Application of Phosphorus and Zinc on Root Configuration, Rhizosphere Soil Nutrients, and Environment of Apple Rootstock M9-T337 Seedlings - Xulin Xian; Wentai Sun; Jietao Zhai; Zhongxing Zhang; Yanlong Gao; Cailong Li; Liang Ding; Yanxiu Wang (Journal of Plant Growth Regulation, 2024)

Varying soil moisture and pH with alpine meadow degradation affect nitrogen preference of dominant species - Chimin Lai; Qiwu Hu; Jianbo Sun; Chengyang Li; Xiaojie Chen; Ben Chen; Xian Xue; Ji Chen; Fujiang Hou; Gang Xu; Wuchen Du; Carly Stevens; et al. (Biology and Fertility of Soils, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Promoter modified hydrophobic core–shell Fe-based catalysts for Fischer-Tropsch synthesis: Enhancing its performance in suppressing water gas shift reaction - Zhuang Ma; Hu Li; Xian Zhang; Fupeng Liu; Jingyi Liu; Hongman Sun; Mingpei Wang; Zhen Liu; Zifeng Yan (Fuel, 2024)

A novel molecular structure parameter determination method for biomass thermochemical conversion mechanism investigation - Liu Shi; Bing Peng; Xian Li; Shuo Li; Yiming Sun; Zhenzhong Hu; Hongyun Hu; Guangqian Luo; Hong Yao (Chemical Engineering Journal, 2024)

Restoration of degraded alpine meadows from the perspective of plant–soil feedbacks - Chengyang Li; Chimin Lai; Fei Peng; Jun Zhou; Wu Zhang; Xiuli Song; Songying Luo; Jianbo Sun; Xiaojie Chen; Ben Chen; Ji Chen; Xian Xue (Biology and Fertility of Soils, 2024)

Experimental and numerical study on NOx reduction from NH3/DME/air flame using fuel staging method - Mingyu Yu; Guangqian Luo; Ruize Sun; Li Wang; Xian Li; Hong Yao (Fuel, 2024)

Polysaccharides in fruits: Biological activities, structures, and structure-activity relationships and influencing factors-A review - Liting Shi; Quan He; Jing Li; Yilong Liu; Yunlin Cao; Yaqin Liu; Chongde Sun; Yuanjiang Pan; Xian Li; Xiaoyong Zhao (Food Chemistry, 2024)

Metabolomics profile of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid-induced brain damage in Carassius auratus and its response to the intestinal microbial community - Xue Jiao; Ning Wang; Lei Guo; Zheng-yao Guo; Xian-wei Hou; Yu-qian Lu; Bao-lan Yao; Jia Sun; Yue-hong Li (Aquaculture, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Ammonia partial cracking over low-cost Ni catalysts for enhancing combustion - Mingyu Yu; Ruize Sun; Guangqian Luo; Li Wang; Xian Li; Hong Yao (Fuel, 2024)

Nitrogen fertilization modulates rice phyllosphere functional genes and pathogens through fungal communities - Wei-Feng Wu; Xin-Yuan Li; Song-Can Chen; Bing-Jie Jin; Chun-Yan Wu; Gang Li; Cheng-liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Science of The Total Environment, 2024)

Optimized dual-gas co-production from hydrate reservoirs with underlying gas through depressurization & well closure cycling: An experimental evaluation - Xian Sun; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Xing-Xun Li; Wei-Xin Pang; Qing-Ping Li; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Occurrence, distribution and sources of microplastics in typical marine recirculating aquaculture system (RAS) in China: The critical role of RAS operating time and microfilter - Zheng Zhou; Xiefa Song; Dengpan Dong; Xian Li; Yue Sun; Liwei Wang; Zhitao Huang; Meng Li (Water Research, 2024)

GABLE: A first fine-grained 3D building model of China on a national scale from very high resolution satellite imagery - Xian Sun; Xingliang Huang; Yongqiang Mao; Taowei Sheng; Jihao Li; Zhirui Wang; Xue Lu; Xiaoliang Ma; Deke Tang; Kaiqiang Chen (Remote Sensing of Environment, 2024)

Multiple stimulus responsive of a novel naphthalenediimide-based 2D alkaline-earth metal MOF material: Hydrochromism, amine-/acid-induced chromism and ionochromism as well as visual artificial film application - Rong Huo; Ting Zhang; Li Xian Sun; Li Na Zhao; Yong Heng Xing; Feng Ying Bai (Chemical Engineering Journal, 2024)

The promotion of the atrazine degradation mechanism by humic acid in a soil microbial electrochemical system - Xinyu Li; Xian Cao; Hui Wang; Yilun Sun; Shuai Zhang; Sirapat Khodseewong; Takashi Sakamaki (Journal of Environmental Management, 2024)

Ultrafine Ru nanoparticles stabilized by V8C7/C for enhanced hydrogen evolution reaction at all pH - Yanju Long; Yong Shen; Pingping Jiang; Hui Su; Jiahui Xian; Yamei Sun; Jun Yang; Haili Song; Qinghua Liu; Guangqin Li (Science Bulletin, 2024)

Natural variation of Grain size 3 allele differentially functions in regulating grain length in xian/indica and geng/japonica rice - Yong-Bin Peng; Chen-Yang Du; Ya-Nan He; Chong-Ke Zheng; Wei Sun; Jin-Jun Zhou; Li-Xia Xie; Cong-Hui Jiang; Jian-Di Xu; Fang Wang; Xian-Zhi Xie (Euphytica, 2024)

Effects of carbon source addition strategies on water quality, growth performance, and microbial community in shrimp BFT aquaculture systems - Yue Sun; Jiasong Zhang; Dengpan Dong; Meng Li; Xiaohan Yang; Xiefa Song; Xian Li (Aquaculture, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

Anthocyanins’ effects on diabetes mellitus and islet transplantation - Yang Liu; Qianwen Wang; Kangze Wu; Zhouyi Sun; Zhe Tang; Xian Li; Bo Zhang (Critical Reviews in Food Science and Nutrition, 2023)

Plasma-assisted synthesis of nano-sulfur adsorbent for efficient removal of mercury from flue gas - Ruize Sun; Guangqian Luo; Mingyu Yu; Li Wang; Xinpei Lu; Xian Li; Hong Yao (Chemical Engineering Journal, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Arterial spin labeling reveals disordered cerebral perfusion and cerebral blood flow-based functional connectivity in primary open-angle glaucoma - Qian Wang; Xiaoxia Qu; Huaizhou Wang; Weiwei Chen; Yunxiao Sun; Ting Li; Jianhong Chen; Yang Wang; Ningli Wang; Junfang Xian (Brain Imaging and Behavior, 2023)
Purpose Primary open-angle glaucoma (POAG) is a widespread neurodegenerative condition affecting brain regions involved in visual processing, somatosensory processing, motor control, emotional regulation and cognitive functions. Cerebral hemodynamic dysfunction contributes to the pathogenesis of glaucomatous neurodegeneration. We aimed to investigate cerebral blood flow (CBF) redistributed patterns in visual and higher-order cognitive cortices and its relationship with clinical parameters in POAG, and we hypothesized that CBF changes together across regions within the same functional network. Methods Forty-five POAG patients and 23 normal controls underwent three-dimensional pseudocontinuous arterial spin labeling MRI to measure the resting-state CBF. Group comparisons of CBF and correlations between CBF changes and ophthalmological and neuropsychological indices were assessed. We determined CBF-based functional connectivity (CBFC) by calculating the correlations between specific regions and all other brain voxels and compared CBFC differences between groups. Results The patients exhibited decreased CBF in visual cortices, postcentral gyrus, inferior parietal lobule and cerebellum and increased CBF in medial, middle, and superior frontal gyri, as well as the insula. The reduced CBF in the visual cortices positively correlated with visual field defect ( r = 0.498, p = 0.001) in POAG patients, while the increased CBF in the right medial frontal gyrus was negatively associated with the visual field defect ( r = −0.438, p = 0.004) and positively associated with the cup-to-disc ratio ( r = 0.469, p = 0.002). POAG patients showed negative connections weakening or converting to mild positive connections, as well as positive connections converting to negative connections. Conclusions Regional and interregional CBF properties confirmed that the aberrant brain regions extend beyond the visual pathway, including the somatosensory, emotional and cognitive networks, which highlights the importance of cerebral hemodynamic dysfunction in the pathophysiology of spreading neurodegeneration in POAG.

The impacts of driving variables on energy-related carbon emissions reduction in the building sector based on an extended LMDI model: a case study in China - Boya Jiang; Lin Sun; Xiaoxiao Zhang; Hong Xian Li; Baolin Huang (Environmental Science and Pollution Research, 2023)

In-memory computing based on photonic-electronic hybrid phase-change cells - Bai-Qian Wang; Xian-Bin Li; Hong-Bo Sun (Science Bulletin, 2023)

Delayed sowing increased dry matter accumulation during stem elongation in winter wheat by improving photosynthetic yield and nitrogen accumulation - Yuangang Zhu; Juan Liu; Jiaqi Li; Lishan Xian; Jinpeng Chu; Hui Liu; Jian Song; Yinghui Sun; Zhongmin Dai (European Journal of Agronomy, 2023)

The formation of proto-austronesians: insights from a revised phylogeography of the paternal founder lineage - Hui-Xin Yu; Xian-Peng Zhang; Yun Bai; Kai-Jun Liu; Hui Li; Yong-Lan Li; Jin Sun; Lan-Hai Wei (Molecular Genetics and Genomics, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Altered stability of dynamic brain functional architecture in primary open-angle glaucoma: a surface-based resting-state fMRI study - Bingbing Yang; Mingyue Su; Qian Wang; Xiaoxia Qu; Huaizhou Wang; Weiwei Chen; Yunxiao Sun; Ting Li; Yang Wang; Ningli Wang; Junfang Xian (Brain Imaging and Behavior, 2023)
Delineating the neuropathological characteristics of primary open-angle glaucoma (POAG) is critical for understanding its pathophysiology. While temporal stability represents a crucial aspect of the brain's functional architecture, the specific patterns underlying its contribution to POAG remain unclear. This study aims to analyze the brain functional abnormalities in POAG using functional stability, a dynamic functional connectivity (DFC) approach based on resting-state functional magnetic resonance imaging (rs-fMRI). Seventy patients with POAG and forty-five healthy controls underwent rs-fMRI and ophthalmological examinations. The stability of DFC was calculated as the concordance of DFC over time using a sliding-window approach, and the differences in stability between the two groups were compared. Subsequently, Spearman’s correlation analyses were conducted to examine the relationship between functional stability and clinical indicators. Compared with healthy controls, patients with POAG exhibited significantly decreased functional stability in the visual network, including the early visual center, ventral and dorsal stream visual cortex in both hemispheres. Conversely, stability values increased in the bilateral inferior parietal gyrus and right inferior frontal cortex. In POAG patients, the dynamic stability of the left early visual cortex and ventral stream visual cortex correlated with the mean deviation of visual field defects ( r = 0.251, p = 0.037). The evidence from this study suggests that functional stability may provide a new understanding of brain alterations in the progression of POAG.

Identifying priority areas for freshwater supply conservation integrating multi-scale freshwater flows - Yan Xu; Hailian Lan; Benyao Wang; Xian Zhao; Dehuan Li; Yixuan Yang; Yujing Xie; Wei Sun (Journal of Environmental Management, 2023)

Lateral impact behaviour of post-fire steel-reinforced concrete-filled steel tubular members: Experiment and evaluation method - Sun-Hang Ji; Wen-Da Wang; Wensu Chen; Yan-Li Shi; Wei Xian (Engineering Structures, 2023)

Visible-light induced tetracycline degradation catalyzed by dual Z-scheme InVO4/CuBi2O4/BiVO4 composites: The roles of oxygen vacancies and interfacial chemical bonds - Jue Liu; Shiwen Li; Can Meng; Jing Sun; Xian Li; Yuanan Hu; Hefa Cheng (Chemical Engineering Journal, 2023)

Earthworms enhance the inhibition efficiency of 3,4-dimethylpyrazole phosphate on soil nitrification by altering soil AOB communities and gut denitrifier communities - Bing-Jie Jin; Xi-Peng Liu; Miao Zhang; Yan Hu; Cheng-Liang Sun; Gang Li; Yong-Guan Zhu; Xian-Yong Lin (Biology and Fertility of Soils, 2023)

Comparative life cycle assessment of whiteleg shrimp (Penaeus vannamei) cultured in recirculating aquaculture systems (RAS), biofloc technology (BFT) and higher-place ponds (HPP) farming systems in China - Yue Sun; Haochen Hou; Dengpan Dong; Jiasong Zhang; Xiaohan Yang; Xian Li; Xiefa Song (Aquaculture, 2023)

Ferritinophagy activation and sideroflexin1-dependent mitochondrial iron overload contribute to patulin-induced cardiac inflammation and fibrosis - Wen-Chang Sun; Ning-Ning Wang; Ru Li; Xian-Ce Sun; Jia-Wei Liao; Guang Yang; Shuang Liu (Science of The Total Environment, 2023)

Corrigendum to “Gas-pressurized torrefaction of biomass wastes: Self-promoted deoxygenation of rice straw at low temperature” [Fuel 308 (2021) 122029] - Yiming Sun; Shan Tong; Xian Li; Zhenzhong Hu; Mingyue Sun; Li Guo; Huan Liu; Hongyun Hu; Guangqian Luo; Hong Yao (Fuel, 2023)

Corrigendum to “Gas-pressurized torrefaction of biomass wastes: The effect of varied pressure on pyrolysis kinetics and mechanism of torrefied biomass” [Fuel 276 (2020) 118132] - Omar D. Dacres; Shan Tong; Xian Li; Yiming Sun; Feng Wang; Guangqian Luo; Huan Liu; Hongyun Hu; Hong Yao (Fuel, 2023)

Generation, activation, and recycling of ammonium persulfate for the remediation of organic-contaminated soil: System construction, process, and mechanisms - Xian Zhu; Wei Sun; Chen Li; Zhenzhen Wang; Xiangfen Cui; Bo Li; Senlin Tian (Chemical Engineering Journal, 2023)

Associations of Blood and Cerebrospinal Fluid Aβ and tau Levels with Renal Function - Hao-Lun Sun; Xiu-Qing Yao; Li Lei; Wang-Sheng Jin; Yu-Di Bai; Gui-Hua Zeng; An-Yu Shi; Jun Liang; Li Zhu; Yu-Hui Liu; Yan-Jiang Wang; Xian-Le Bu (Molecular Neurobiology, 2023)

Dual-gas co-production behavior for hydrate-bearing coarse sediment with underlying gas via depressurization under constrained conditions - Xian Sun; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Xing-Xun Li; Wei-Xin Pang; Qing-Ping Li; Chang-Yu Sun; Guang-Jin Chen (Gas Science and Engineering, 2023)

Exposure to outdoor artificial light at night increases risk and burden of metabolic disease in Ningxia, China - Huihui Wang; Xiaohong Ma; Zhenfan Yu; Naifan Hu; Yurun Du; Xiaoxue He; Degong Pan; Lining Pu; Xue Zhang; Xian Sun; Jiangping Li (Environmental Science and Pollution Research, 2023)

Analysis of proanthocyanidins and flavonols in the seedpods of Chinese Antique Lotus: A rich source of antioxidants - Xiaohan Wang; Bing Li; Shanshan Sun; Qingqing Liu; Jin Zhu; Xian Zhou; Huijin Zhang; Qian Wu; Liangsheng Wang (Food Chemistry, 2023)

Hysteretic behavior of post-tensioned precast segmental CFT double-column piers - Xian Li; Zilin Zhang; Tao Zhou; Yu Xiao; Yushun Sun (Earthquake Engineering and Engineering Vibration, 2023)

Microplastics exhibit accumulation and horizontal transfer of antibiotic resistance genes - Yue Feng; Jia-Wen Sun; Wei-Wei Shi; Jian-Lu Duan; Xiao-Dong Sun; Li-Juan Feng; Qian Wang; Yu-Dong Gan; Xian-Zheng Yuan (Journal of Environmental Management, 2023)

Rational design of one inorganic-organic hybrid Z-scheme heterojunction for high-performance photocatalytic water splitting - Cun-biao Lin; Fu-li Sun; Jun Wen; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2023)

Potential Therapeutic Effects of Policosanol from Insect Wax on Caenorhabditis elegans Models of Parkinson’s Disease - Chenjing Ma; Ying Feng; Xian Li; Long Sun; Zhao He; Jin Gan; Minjie He; Xin Zhang; Xiaoming Chen (Journal of Neuroimmune Pharmacology, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

OGMN: Occlusion-guided multi-task network for object detection in UAV images - Xuexue Li; Wenhui Diao; Yongqiang Mao; Peng Gao; Xiuhua Mao; Xinming Li; Xian Sun (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Characterization of anthocyanin accumulation, nutritional properties, and postharvest attributes of transgenic purple tomato - Wei Jian; Xiaogang Ou; Lixinyu Sun; Yu Chen; Shiyu Liu; Wang Lu; Xian Yang; Zhengwu Zhao; Zhengguo Li (Food Chemistry, 2023)

Structural construction of Bi-anchored honeycomb N-doped porous carbon catalyst for efficient CO2 conversion - Huaxin Li; Kelong Ao; Jiapeng Liu; Fenglei Sun; Xianbo Yu; Xiangyang Zhang; Jihong Shi; Xian Yue; Junhui Xiang (Chemical Engineering Journal, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

An environmentally insensitive fluorescent probe for G4 DNA detection: Design, synthesis, and mechanism studies - Xue-Xian Lang; Shu-Hui Sun; Hao-Wen Cao; Yan-Song Chen; Hong-Yao Li; Ming-Qi Wang (Analytica Chimica Acta, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Polyethylene and poly (butyleneadipate-co-terephthalate)-based biodegradable microplastics modulate the bioavailability and speciation of Cd and As in soil: Insights into transformation mechanisms - Chaohang Li; Huarong Sun; Yilan Shi; Zhengxiong Zhao; Zhen Zhang; Ping Zhao; Qiyan Gao; Xian Zhang; Bin Chen; Yongtao Li; Shuran He (Journal of Hazardous Materials, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Occurrence, partition behavior, source and ecological risk assessment of nitro-PAHs in the sediment and water of Taige Canal, China - Jijie Kong; Tao Ma; Xiaoyu Cao; Weidi Li; Fengxiao Zhu; Huan He; Cheng Sun; Shaogui Yang; Shiyin Li; Qiming Xian (Journal of Environmental Sciences, 2023)

Predicting the bioavailability of nitro polycyclic aromatic hydrocarbons in sediments: ZIF-8/h-BN solid-phase microextraction versus Tenax extraction - Jijie Kong; Xiaoyu Cao; Wen Huang; Chao Li; Qiming Xian; Shaogui Yang; Shiyin Li; Cheng Sun; Huan He (Environmental Pollution, 2023)

Development and application of a multiplex qPCR assay for the detection of duck circovirus, duck Tembusu virus, Muscovy duck reovirus, and new duck reovirus - Yan Wen Yin; Chenyong Xiong; Kai Chuang Shi; Shou Yu Xie; Feng Long; Jun Li; Min Zheng; Xian Kai Wei; Shuping Feng; Sujie Qu; Wenjun Lu; Hongjin Zhou; et al. (Virus Genes, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

A ca. 290 Ma hydrothermal calcite in Cambrian dolostone - Zhongwu Lan; Shitou Wu; Fangyue Wang; Bo Liu; Kaibo Shi; Jing Sun; Rong Cao; Xian-Hua Li (Marine and Petroleum Geology, 2023)

Modified flood potential index (MFPI) for flood monitoring in terrestrial water storage depletion basin using GRACE estimates - Wei Jiang; Xuan Ji; Yungang Li; Xian Luo; Luyi Yang; Wenting Ming; Chang Liu; Siyi Yan; Chuanjian Yang; Cezong Sun (Journal of Hydrology, 2023)

Plasticity in over-compensatory growth along an alpine meadow degradation gradient on the Qinghai-Tibetan Plateau - Fei Peng; Chimin Lai; Chengyang Li; Chen Ji; Pengfei Zhang; Jianbo Sun; Xiaojie Chen; Quangang You; Xian Xue (Journal of Environmental Management, 2023)

Height aware understanding of remote sensing images based on cross-task interaction - Yingchao Feng; Xian Sun; Wenhui Diao; Jihao Li; Ruigang Niu; Xin Gao; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Honeycomb-like N/O self-doped hierarchical porous carbons derived from low-rank coal and its derivatives for high-performance supercapacitor - Li Li; Xian-Yong Wei; Chang-Wang Shao; Fan Yin; Bing-Kang Sun; Fang-Jing Liu; Jia-Hao Li; Zhong-Qiu Liu; Zhi-Min Zong (Fuel, 2023)

O-hetero-Fe-N3.6 active sites in ZIF-derived carbon nanotubes for the electrocatalytic oxygen evolution reaction - Xian Yang; Jun Cheng; Xiao Yang; Yang Xu; Hao Li; Weifu Sun; Weifeng Tu; Junhu Zhou (Chemical Engineering Journal, 2023)

Constructing hollowly bimetallic selenides as cathode for aqueous zinc battery with outstanding rate performance - Hui Gao; Xixi Zhang; Gang Sun; Chuanlin Li; Xijin Xu; Xian Zhao (Chemical Engineering Journal, 2023)

Optimization and understanding of ZnO nanoarray supported Cu-ZnO-Al2O3 catalyst for enhanced CO2 -methanol conversion at low temperature and pressure - Jiyu Sun; Fangyuan Liu; Usman Salahuddin; Mudi Wu; Chunxiang Zhu; Xingxu Lu; Bo Zhang; Binchao Zhao; Zhiqiang Xie; Yunjiang Ding; Dongsheng Li; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2023)

Smartphone bioelectronic drug with visual colorimetric sensor and bulk nanoencapsulation optogenetic bacteria for chronic kidney disease theragnostics - Meihui Cui; Wei Ling; Lili Zhang; Yayang Li; Jing Liu; Tao Sun; Binglin Ma; Shenjunjie Lu; Huizhuo Pan; Gaoju Pang; Yingying Zhang; Shufang Zhang; et al. (Chemical Engineering Journal, 2023)

Correction to: Niche differentiation and higher uptake of available nitrogen maintained the productivity of alpine meadow at early degradation - Chimin Lai; Fei Peng; Jianbo Sun; Jun Zhou; Chengyang Li; Xingliang Xu; Xiaojie Chen; Quangang You; Hongyang Sun; Jian Sun; Xian Xue; Hans Lambers (Biology and Fertility of Soils, 2023)

Niche differentiation and higher uptake of available nitrogen maintained the productivity of alpine meadow at early degradation - Chimin Lai; Fei Peng; Jianbo Sun; Jun Zhou; Chengyang Li; Xingliang Xu; Xiaojie Chen; Quangang You; Hongyang Sun; Jian Sun; Xian Xue; Hans Lambers (Biology and Fertility of Soils, 2023)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

Awareness for Endoscopic Screening Among Accompanying Children of Hospitalized Esophageal Cancer Patients in Henan - Lian Qun Zhang; Xian Juan Du; Fu You Zhou; Pei Nan Chen; Hai Ling Wang; Li Sun; Xiu Ling Li (Journal of Cancer Education, 2022)

LncRNA BIRF Promotes Brain Ischemic Tolerance Induced By Cerebral Ischemic Preconditioning Through Upregulating GLT-1 via Sponging miR-330-5p - Shichao Li; Lingyan Zhang; Jiajie Lin; Achou Su; Xiyun Liu; Jingge Zhang; Xiaohui Xian; Yuyan Hu; Wenbin Li; Shaoguang Sun; Min Zhang (Molecular Neurobiology, 2022)
Long noncoding RNAs (lncRNAs) play an important regulatory role in various diseases. However, the role of lncRNAs in brain ischemic tolerance (BIT) induced by cerebral ischemic preconditioning (CIPC) is still unknown. The lncRNA profile of rat cortical astrocytes pretreated with ischemic preconditioning was analyzed by high-throughput sequencing. The results of Cell-Counting Kit-8 (CCK-8) assay showed that a novel lncRNA, NONRATT009133.2, which we referred to as brain ischemia–related factor (BIRF), was highly correlated with BIT. Through bioinformatics analysis, we predicted that BIRF, miR-330-5p, and GLT-1 (also named Slc1a2 ) might constitute a ceRNA regulatory network in the induction of BIT. We found that BIRF was upregulated by CIPC, which promoted GLT-1 expression and BIT induction. BIRF could directly bind to miR-330-5p. Furthermore, miR-330-5p directly targeted GLT-1, and miR-330-5p inhibited both GLT-1 expression and BIT induction in vitro and in vivo. Moreover, BIRF acts as a molecular sponge to competitively bind to miR-330-5p with GLT-1 mRNA, while the miR-330-5p inhibitor reversed all the effects of BIRF siRNA on GLT-1 expression and neuronal vitality. Taken together, our results demonstrate the important roles of the BIRF/miR-330-5p/GLT-1 axis in the induction of BIT by CIPC. BIRF may be a potentially effective therapeutic strategy against stroke injury.

Formation and reactivation mechanisms of large-scale ancient landslides in the Longwu River basin in the northeast Tibetan Plateau, China - Jing-jing Tian; Tian-tao Li; Xiang-jun Pei; Feng Ding; Hao Sun; Xian-gang Xie; Jian Guo (Journal of Mountain Science, 2022)

Citrus flavonoids and their antioxidant evaluation - Yue Wang; Xiao-Juan Liu; Jie-Biao Chen; Jin-Ping Cao; Xian Li; Chong-De Sun (Critical Reviews in Food Science and Nutrition, 2022)

Fine mapping of Pm58 from Aegilops tauschii conferring powdery mildew resistance - Shulin Xue; Shanshan Hu; Xian Chen; Yuyu Ma; Mingxue Lu; Shenglong Bai; Xintian Wang; Tiepeng Sun; Yingxue Wang; Hongshen Wan; Xia An; Suoping Li (Theoretical and Applied Genetics, 2022)

Study of the heterologous gene expression characteristics of a new clone of a cell line derived from Papilio xuthus and its serum-free adaptation - Wei-Feng Ding; Na Sun; Zhi-Gang Liu; Xin Zhang; Xian Li; Hang Chen; Ying Feng (In Vitro Cellular & Developmental Biology - Animal, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

Efficacy and safety of aripiprazole once-monthly versus oral aripiprazole in Chinese patients with acute schizophrenia: a multicenter, randomized, double-blind, non-inferiority study - Le Xiao; Qian Zhao; An-ning Li; Jushui Sun; Bin Wu; Lina Wang; Honggeng Zhang; Ruiling Zhang; Keqing Li; Xiaojin Xu; Tiebang Liu; Wenshun Zhang; et al. (Psychopharmacology, 2022)

Inoculation with Rhizobacteria Enhanced Tolerance of Tomato (Solanum lycopersicum L.) Plants in Response to Cadmium Stress - Ting Wei; Yanni Sun; Noman Yashir; Xian Li; Junkang Guo; Xun Liu; HongLei Jia; Xinhao Ren; Li Hua (Journal of Plant Growth Regulation, 2022)

Soil amendments inhibited the cadmium accumulation in Ligusticum striatum DC. and improved the plant growth - Xian Xiao; Meng Pei; Junjie Zhou; Shuo Sun; Chengcheng Li; Xuesong Zhu; Yuan Zhao (Environmental Science and Pollution Research, 2021)

Mobilization of soil phosphate after 8 years of warming is linked to plant phosphorus‐acquisition strategies in an alpine meadow on the Qinghai‐Tibetan Plateau - Jun Zhou; Xiao‐Long Li; Fei Peng; Chengyang Li; Chimin Lai; Quangang You; Xian Xue; Yanhong Wu; Hongyang Sun; Yang Chen; Hongtao Zhong; Hans Lambers (Global Change Biology, 2021)
Phosphorus (P) is essential for productivity of alpine grassland ecosystems, which are sensitive to global warming. We tested the hypotheses that (1) mobilized ‘calcium‐bound inorganic P’ (Ca‐P i ) is a major source of plant‐available P in alpine meadows with alkaline soils after long‐term warming, (2) mobilization of Ca‐P i is linked to effective plant carboxylate‐releasing P‐acquisition strategies under warming, and (3) the mobilization is also related to plant nitrogen (N)‐acquisition. We conducted an 8‐year warming experiment in an alpine meadow (4635 m above sea level) on the Qinghai‐Tibetan Plateau. A significant increase in P concentration in both aboveground and belowground biomass indicates an increased mobilization and assimilation of P by plants under warming. We observed a significant decrease in Ca‐P i , no change in moderately‐labile organic P, and an increase in highly resistant organic P after warming. There was no increase in phosphatase activities. Our results indicate that Ca‐P i , rather than organic P was the major source of plant‐available P for alpine meadows under warming. Higher leaf manganese concentrations of sedges and forbs after warming indicate that carboxylates released by these plants are a key mechanism of Ca‐P i mobilization. The insignificant increase in Rhizobiales after warming and the very small cover of legumes show a minor role of N‐acquisition strategies in solubilizing phosphate. The insignificant change in relative abundance of mycorrhizal fungi and bacteria related to P cycling after warming shows a small contribution of microorganisms to Ca‐P i mobilization. The significant increase in leaf N and P concentrations and N:P ratio of grasses and no change in sedge leaf N:P ratio reflect distinct responses of plant nutrient status to warming due to differences in P‐acquisition strategies. We highlight the important effects of belowground P‐acquisition strategies, especially plant carboxylate‐releasing P‐acquisition strategies on responses of plants to global changes in alpine meadows.

Spatiotemporal change of vegetation coverage recovery and its driving factors in the Wenchuan earthquake-hit areas - Xiao-fei Sun; Lin-guo Yuan; Ying-zhi Zhou; Huai-yong Shao; Xian-feng Li; Ping Zhong (Journal of Mountain Science, 2021)

Effect of exogenous silicon and methyl jasmonate on the alleviation of cadmium-induced phytotoxicity in tomato plants - Ting Wei; Xian Li; Noman Yashir; Hong Li; Yanni Sun; Li Hua; Xinhao Ren; Junkang Guo (Environmental Science and Pollution Research, 2021)

Ruania alkalisoli sp. nov., Isolated from Saline–Alkaline Soil - Ji-Quan Sun; Pa Eryang Yiayeng; Lian Xu; Xiao-Xian Huang; Yan Li (Current Microbiology, 2021)

A hierarchical genetic algorithm and mixed-integer linear programming-based stochastic optimization of the configuration of integrated trigeneration energy systems - Yisong Zhang; Jingjing Jiang; Xian Zhang; Li Sun (Clean Technologies and Environmental Policy, 2021)

Characterization of the pectin methylesterase inhibitor gene family in Rosaceae and role of PbrPMEI23/39/41 in methylesterified pectin distribution in pear pollen tube - Xiaoxuan Zhu; Chao Tang; Qionghou Li; Xin Qiao; Xian Li; Yilin Cai; Peng Wang; Yangyang Sun; Hua Zhang; Shaoling Zhang; Juyou Wu (Planta, 2021)

Structural Variability and Functional Prediction in the Epiphytic Bacteria Assemblies of Myriophyllum spicatum - Ling Xian; Tao Wan; Yu Cao; Junyao Sun; Ting Wu; Andrew Apudo Apudo; Wei Li; Fan Liu (Current Microbiology, 2020)

Phaeotremella camelliae sp. nov. (Phaeotremellaceae, Tremellales), A Novel Yeasts Isolated from Tea-Oil Fruits in Jiangxi Province, China - Yong Sun; Gui-Shuang Wang; Ai-Hua Li; Wangmu; Xian-Qiu Chui; Ji-Hong Jiang; Qi-Ming Wang (Current Microbiology, 2020)

The association between dioxins and steroid hormones in general adult males: a cross-sectional study in an e-waste region of China - Li Li Shi; Mei Qin Wang; Shoji F. Nakayama; Chau-Ren Jung; Yue Hua Wang; Jing Jian Dong; Chao Chen Ma; Teruhiko Kido; Xian Liang Sun; Hao Feng (Environmental Science and Pollution Research, 2020)

Inhibition of glycolysis ameliorate arthritis in adjuvant arthritis rats by inhibiting synoviocyte activation through AMPK/NF-кB pathway - Ying Wang; Hao Xian; Jiajia Qi; Fang Wei; Xiu Cheng; Sha Li; Qing Wang; Zhaoyang Liu; Yun Yu; Jing Zhou; Xiaojin Sun; Hao Liu; et al. (Inflammation Research, 2020)

Screening of single-cell clonal lines from Papilio demoleus Linnaeus cell lines for exogenous protein expression and adaptation in serum-free culture - Wei-Feng Ding; Zhi-Gang Liu; Na Sun; Xin Zhang; Xian Li; Ying Feng (In Vitro Cellular & Developmental Biology - Animal, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Seismic design and behavior of self-centering energy dissipation braced steel frame - Long-He Xu; Yu-Sheng Sun; Xiao-Wei Fan; Zhong-Xian Li (Bulletin of Earthquake Engineering, 2020)

v301, a new allele of BRITTLE CULM 12, and its regulation of the early senescence of the leaf blade in rice - Ji-le Ni; Xiao-zhu Wen; Cheng-bing Tang; Wei-jiang Tian; Wen-jing Yang; Jia Xie; Xiao-bo Zhang; Yang-yang Li; Yu-zhen Xiong; Ying Sun; Zhu Zhu; Ying Wang; et al. (Acta Physiologiae Plantarum, 2020)

China-France Oceanography Satellite (CFOSAT) simultaneously observes the typhoon-induced wind and wave fields - Ying Xu; Jianqiang Liu; Lingling Xie; Congrong Sun; Jinpu Liu; Junyi Li; Di Xian (Acta Oceanologica Sinica, 2019)

Induced Intermediate Mesoderm Combined with Decellularized Kidney Scaffolds for Functional Engineering Kidney - Jianye Zhang; Kailin Li; Feng Kong; Chao Sun; Denglu Zhang; Xin Yu; Xuesheng Wang; Xian Li; Tongyan Liu; Guangfeng Shao; Yong Guan; Shengtian Zhao (Tissue Engineering and Regenerative Medicine, 2019)

Fusarium oxysporum KB-3 from Bletilla striata: an orchid mycorrhizal fungus - Jianwei Jiang; Ke Zhang; Sheng Cheng; Qianwen Nie; Shen-xian Zhou; Qingqing Chen; Jinglong Zhou; Xiao Zhen; Xue ting Li; Tong wen Zhen; Mingyue Xu; Tom Hsiang; et al. (Mycorrhiza, 2019)

Effects of perinatal dioxin exposure on development of children: a 3-year follow-up study of China cohort - Zheng Wang; Jin Guo Hang; Hao Feng; Li Li Shi; Jing Jian Dong; Bin Shen; Ting Luo; Ren Mei Cai; Ling Jie Shen; Teruhiko Kido; Xian Liang Sun (Environmental Science and Pollution Research, 2019)

Garnet amphibolites from the Ganzi–Litang fault zone, eastern Tibetan Plateau: mineralogy, geochemistry, and implications for evolution of the eastern Palaeo-Tethys Realm - Qiu-Huan Li; Yu-Xiu Zhang; Kai-Jun Zhang; Li-Long Yan; Lu Zeng; Xin Jin; Jin-Feng Sun; Xiao-Yao Zhou; Xian-Chun Tang; Lu Lu (International Geology Review, 2018)

Clinical Research on Alzheimer’s Disease: Progress and Perspectives - Bin-Lu Sun; Wei-Wei Li; Chi Zhu; Wang-Sheng Jin; Fan Zeng; Yu-Hui Liu; Xian-Le Bu; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang (Neuroscience Bulletin, 2018)

Occurrence and distribution of antibiotic resistance genes in the sediments of drinking water sources, urban rivers, and coastal areas in Zhuhai, China - Aolin Li; Lujun Chen; Yan Zhang; Yile Tao; Hui Xie; Si Li; Weiling Sun; Jianguo Pan; Zhidong He; Chaoan Mai; Yingying Fan; Huanchao Xian; et al. (Environmental Science and Pollution Research, 2018)

Development of chloroplast genomic resources for Pyrus hopeiensis (Rosaceae) - Wenqing Li; Yizeng Lu; Xiaoman Xie; Bin Li; Yi Han; Tao Sun; Yang Xian; Haiping Yang; Kun Liu (Conservation Genetics Resources, 2018)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Genetic mapping and salt tolerance of a novel D1-allelic mutant of rice (Oryza sativa L.) - Wei-jiang Tian; Xiao-qiong Zhang; Xiao-wen Wang; Jia Xie; Yang-yang Li; Ying Sun; Yi-ran Tao; Yu-zhen Xiong; Xian-chun Sang (Acta Physiologiae Plantarum, 2018)

Intestinal microbiota of healthy and unhealthy Atlantic salmon Salmo salar L. in a recirculating aquaculture system - Chun Wang; Guoxiang Sun; Shuangshuang Li; Xian Li; Ying Liu (Journal of Oceanology and Limnology, 2018)

Temporal patterns and processes of genetic differentiation of the Brachionus calyciflorus (Rotifera) complex in a subtropical shallow lake - Ye Zhang; Ao Zhou; Yi-Long Xi; Qiang Sun; Le-Feng Ning; Ping Xie; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Functional characterization of the promoter of carbonyl reductase 1 gene in porcine endometrial cells - Ai-ling Zhang; Xian-yue Sun; Qi Yin; Jian-hua Zeng; Zhe Zhang; Jia-qi Li; Hao Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

C-myc overexpression drives melanoma metastasis by promoting vasculogenic mimicry via c-myc/snail/Bax signaling - Xian Lin; Ran Sun; Xiulan Zhao; Dongwang Zhu; Xueming Zhao; Qiang Gu; Xueyi Dong; Danfang Zhang; Yanhui Zhang; Yanlei Li; Baocun Sun (Journal of Molecular Medicine, 2017)

Endosulfan inhibiting the meiosis process via depressing expressions of regulatory factors and causing cell cycle arrest in spermatogenic cells - Fang-Zi Guo; Lian-Shuang Zhang; Jia-Liu Wei; Li-Hua Ren; Jin Zhang; Li Jing; Man Yang; Ji Wang; Zhi-Wei Sun; Xian-Qing Zhou (Environmental Science and Pollution Research, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

Application of a weak magnetic field to improve microbial fuel cell performance - Zhong-Hua Tong; Han-Qing Yu; Wen-Wei Li; Yun-Kun Wang; Min Sun; Xian-Wei Liu; Guo-Ping Sheng (Ecotoxicology, 2015)

Simulating the effects of chemical and non-chemical fertilization practices on carbon sequestration and nitrogen loss in subtropical paddy soils using the DNDC model - Hou-Xi Zhang; Bo Sun; Xian-Li Xie; Shun-Yao Zhuang (Paddy and Water Environment, 2015)

Evaluation of feed and feeding regime on growth performance, flesh quality and fecal viscosity of Atlantic salmon (Salmo salar L.) in recirculating aquaculture systems - Guoxiang Sun; Ying Liu; Yong Li; Xian Li; Shunkui Wang (Journal of Ocean University of China, 2015)

TGF-β1 and TIMP-4 regulate atrial fibrosis in atrial fibrillation secondary to rheumatic heart disease - Yu Sun; Zi-Yang Huang; Zhen-Hua Wang; Cui-Ping Li; Xian-Liang Meng; Yun-Jiao Zhang; Feng Su; Nan Ma (Molecular and Cellular Biochemistry, 2015)

Variation of levels and distribution of N-nitrosamines in different seasons in drinking waters of East China - Ting Li; Dian Yu; Qiming Xian; Aimin Li; Cheng Sun (Environmental Science and Pollution Research, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Advanced glycation end products promote proliferation and suppress autophagy via reduction of Cathepsin D in rat vascular smooth muscle cells - Mingfeng Ma; Xiaofan Guo; Ye Chang; Chao Li; Xin Meng; Si Li; Zhen-Xian Du; Hua-Qin Wang; Yingxian Sun (Molecular and Cellular Biochemistry, 2015)

Acutissimanide, a new lignan with antioxidant activity isolated from the bark of Quercus acutissima Carruth - Xiao-Li Zeng; Guang-Miao Fu; Kai Tian; Jing-Xian Sun; Hua-Bin Xiong; Xiang-Zhong Huang; Zhi-Yong Jiang (Natural Product Research, 2014)

Seohaeicola westpacificensis sp. nov., A Novel Member of Genera Seohaeicola Isolated from Deep West Pacific Sea Water - Shuhui Xian; Rui Zhang; Jia Sun; Yi Chen; Wenchao Deng; Shuhui Li; Nianzhi Jiao (Current Microbiology, 2014)

Asiatic Acid Inhibits Adipogenic Differentiation of Bone Marrow Stromal Cells - Zheng-Wei Li; Cheng-dong Piao; Hong-Hui Sun; Xian-Sheng Ren; Yun-Shen Bai (Cell Biochemistry and Biophysics, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Suppression of Autophagy Enhanced Growth Inhibition and Apoptosis of Interferon-β in Human Glioma Cells - Yubin Li; Haiyan Zhu; Xian Zeng; Jiajun Fan; Xiaolu Qian; Shaofei Wang; Ziyu Wang; Yun Sun; Xiaodan Wang; Weiwu Wang; Dianwen Ju (Molecular Neurobiology, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Relationship Between Myocardial Bridging and Coronary Arteriosclerosis - Jian Ling Sun; Wei Min Huang; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Genetic variations of ANGPTL6 gene and their associations with growth traits and slaughter traits in Qinchuan cattle - Ai-Min Li; Xian-Yong Lan; Xiao-Mei Sun; Yuan Gao; Wei Ma; Yun Ma; Hong Chen (Molecular Biology Reports, 2012)

Fertilization increases paddy soil organic carbon density - Shao-xian Wang; Xin-qiang Liang; Qi-xiang Luo; Fang Fan; Ying-xu Chen; Zu-zhang Li; Huo-xi Sun; Tian-fang Dai; Jun-nan Wan; Xiao-jun Li (Journal of Zhejiang University-SCIENCE B, 2012)

Aspirin Protects Dopaminergic Neurons Against Lipopolysaccharide-Induced Neurotoxicity in Primary Midbrain Cultures - Fang Wang; Heng Zhai; Luqi Huang; Hui Li; Yan Xu; Xian Qiao; Shenggang Sun; Yan Wu (Journal of Molecular Neuroscience, 2012)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Expression of Trichoderma viride endoglucanase III in the larvae of silkworm, Bombyx mori L. and characteristic analysis of the recombinant protein - Xing-hua Li; Peng Zhang; Mei-xian Wang; Fang Zhou; Firdose Ahmad Malik; Hua-jun Yang; Roy Bhaskar; Jia-biao Hu; Chun-guang Sun; Yun-gen Miao (Molecular Biology Reports, 2011)

The mechanism for heme to prevent Aβ1–40 aggregation and its cytotoxicity - Qingui Bao; Ying Luo; Wei Li; Xiaobo Sun; Cuiqing Zhu; Pingwei Li; Zhong-Xian Huang; Xiangshi Tan (JBIC Journal of Biological Inorganic Chemistry, 2011)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Synthesis and Luminescence Properties of Two Novel Lanthanide (III) Perchlorate Complexes with Bis(benzoylmethyl) Sulfoxide and Benzoic Acid - Wen-Xian Li; Wen-Juan Chai; Xiao-Jun Sun; Tie Ren; Xiao-Yan Shi (Journal of Fluorescence, 2010)

The Studies of Enhanced Fluorescence in the Two Novel Ternary Rare-Earth Complex Systems - Xiao-Jun Sun; Wen-Xian Li; Wen-Juan Chai; Tie Ren; Xiao-Yan Shi (Journal of Fluorescence, 2010)

A single-nucleotide polymorphism of the TNFAIP3 gene is associated with systemic lupus erythematosus in Chinese Han population - Li-Qiong Cai; Zai-Xing Wang; Wen-Sheng Lu; Jian-Wen Han; Liang-Dan Sun; Wen-Hui Du; Shu-Mei Zhang; Xian-Bo Zuo; Xue-Jun Zhang; Sen Yang (Molecular Biology Reports, 2010)

Synthesis and Fluorescence Properties of Lanthanide (III) Perchlorate Complexes with Naphthyl-Naphthalinesulphonylpropyl Sulfoxide - Wen-Xian Li; Yu-Shan Zheng; Xiao-Jun Sun; Xiao-Yan Shi; Wen-Juan Chai; Tie Ren (Journal of Fluorescence, 2010)

Effects of Gestational Cadmium Exposure on Pregnancy Outcome and Development in the Offspring at Age 4.5 Years - Li-Li Tian; Yong-Cheng Zhao; Xiao-Chun Wang; Jin-Long Gu; Zhi-Juan Sun; Ya-Li Zhang; Ji-Xian Wang (Biological Trace Element Research, 2009)

Charge Transfer Photophysics of Tetra(α-amino) Zinc Phthalocyanine - Xian-Fu Zhang; Xijiang Li; Lihong Niu; Lou Sun; Lu Liu (Journal of Fluorescence, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Characterization of cDNAs associated with lignification and their expression profiles in loquat fruit with different lignin accumulation - Lan Lan Shan; Xian Li; Ping Wang; Chong Cai; Bo Zhang; Chong De Sun; Wang Shu Zhang; Chang Jie Xu; Ian Ferguson; Kun Song Chen (Planta, 2008)

The effect of nitric oxide on metal release from metallothionein-3: gradual unfolding of the protein - Hui Wang; Hongyan Li; Bin Cai; Zhong-Xian Huang; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2008)

Retention capacities of several bryophytes for Hg(II) with special reference to the elevation and morphology of moss growth - Shou-Qin Sun; Ding-Yong Wang; Ming He; Xian-Yuan Li; Cheng Zhang (Environmental Monitoring and Assessment, 2007)

A new nor-lignan from the seeds of Descurainia sophia - Kai Sun; Xian Li; Wen Li; Jian-Ming Liu; Jin-Hui Wang; Yi Sha (Natural Product Research, 2006)

Cloning and characterization of a gene for an LRR receptor-like protein kinase associated with cotton fiber development - Yuan-Li Li; Jie Sun; Gui-Xian Xia (Molecular Genetics and Genomics, 2005)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.